(untitled) (Journal of the College of Basic Education, 2023)
The current research aimed to identify (patterns beyond emotion among primary school mathematics teachers) and to achieve this, the researcher chose a random sample of (60) teachers from governmental primary schools affiliated to the Baghdad / Karkh district, and the data was processed by statistical means using the statistical bag ( (Spss) in the procedures and data analysis of the current research. The researcher concluded that: Elementary school mathematics teachers enjoy a positive style in dealing with students’ emotions represented by the emotion education (training) style.